Bagous obrieni (Coleoptera: Curculionidae), a new species from India feeding on Nymphoides indica (L.) Kuntze - Govindasamy, Mahendiran; Gopinath, Poornima; Caldara, Roberto; Boraiah, Manu; Sushil, Satya Nand (Zootaxa, 2025)
A new species, Bagous obrieni Mahendiran sp. nov., is described. It was collected from Nymphoides indica (L.) Kuntze, in Nayakanapalya Lake at Savandurga, Karnataka, South-Western India. The species is a member of the Bagous transversus species group and description and photographs of differential diagnostic characters and habitus are given allowing for separation from the other two Indian species of this group, B. loisae O’Brien and B. similis O’Brien. An annotated species checklist of the genus Bagous from India is also provided.